Effect of extremely high frequency EMI on lipid peroxidation and activietes of antioxidant enzymes of wheat shoots - Zh. H. Mukhaelyan; G. H. Poghosyan; P. H. Vardevanyan (ՀՀ ԳԱԱ հրատ.)
The investigation of the electromagnetic irradiation (EMI) with extremely high frequencies (EHF)- 41.8 GHz, 42.2 GHz, 50.3 GHz and 51.8 GHz and low intensity flux capacity (0.6 mW.cm-2 ) of seeds and growth of germs of wheat (Triticum aestivum L.) has been carried out. The effect of EMI on lipid peroxidation and antioxidant system function of wheat shoot cells has been also studied. It has been shown that at irradiation of germinating seeds the increasing of wheat germ mass as well as lipid peroxidation rate is observed. At the same time EMI-induced oxidative stress was indicated by the markedly change of catalase (CAT) activity depending on EMI frequency used and exposure duration. Ուսումնասիրվել է ծայրահեղ բարձր հաճախականության (ԾԲՀ)- 41.8 ԳՀց, 42.2 ԳՀց, 50.3 ԳՀց և 51.8 ԳՀց և ցածր հոսքի խտությամբ՝ 0.6 մՎտ.սմ-2 էլեկտրամագնիսական ճառագայթման (ԷՄՃ) ազդեցությունը ցորենի (Triticum aestivum L.) ծիլերի աճի վրա: Հետազոտվել է նաև ԷՄՃ ազդեցությունը ցորենի ծիլերի բջիջներում լիպիդների պերօքսիդային օքսիդացման ինտենսիվության և հակաօքսիդանտային համակարգի ֆունկցիաների վրա: Ցույց է տրվել, որ ծլող սերմերի ճառագայթահարումը բերում է ծիլերի զանգվածի, դրանցում լիպիդների պերօքսիդային օքսիդացման ինտենսիվության աճի: ԷՄՃ-ինդուկցված օքսիդատիվ սթրեսը արտահայտվում է նաև կատալազի ակտիվության նշանակալի փոփոխությամբ՝ կախված կիրառված հաճախականությունից և ճառագայթահարման տևողությունից: Исследовалось влияние ЭМИ КВЧ-диапазона (41.8 ГГц, 42.2 ГГц, 50.3 ГГц и 51.8 ГГц) с плотностью потока мощности 0.6 мВт.см-2 на рост семян пшеницы (Triticum aestivum L.). Изучалось также воздействие ЭМИ на интенсивность процессов перекисного окисления липидов и функционирование антиоксидантной системы клеток проростков пшеницы. Установлено, что облучение прорастающих семян приводит к увеличению массы проростков и к усилению перекисного окисления липидов. При этом индуцированный ЭМИ оксидативный стресс приводил к определенному изменению активности каталазы в зависимости от частоты и длительности ЭМИ-воздействия.
Keywords: Biology; Biophysics